Analisis pertumbuhan tiga kultivar kacang tunggak growth analysis of three cowpea cultivars - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Growth analysis of three cowpea cultivars differing in their growth habit: KT 1 (determinate), KT 4 (semi-determinate) and UGM 2 (indeterminate) revealed differences in terms of maximum weight and growth rate: indeterminate cowpea cultivar has higher values compared to the other two which are similar to each other. As proportion, however, growth rate to their respective maximum weight value is comparable for the three cowpea cultivars.